Kesesuaian Akad Salam Pada Fitur Pre order Tokopedia - ahmad Muhammad al maghrobi; Salman Al farisi; Lukmanul hakim; Reza hilmy luayyin (Wasīlah: Journal Of Sharia Sciences, 2025)
This research analyzes the suitability of the salam contract with the pre-order system in Tokopedia . The pre-order   system in Tokopedia  allows buyers to order goods that are not yet available, with the seller promising to deliver them at a later date and payment is often made in advance. This mechanism shows similarities with the concept of a salam contract in fiqh muamalah, which is a sale and purchase contract in which payment is made in advance for goods that will be delivered in the future.However, to ensure Shariah compliance, it is important to observe the unique characteristics of Tokopedia 's pre-order   system. This analysis focuses on the potential alignments and differences between the two. While there are fundamental similarities regarding upfront payment and delivery of goods at a later date, some aspects require more attention. These include issues such as item specifications, delivery timeframes, risk of transaction cancellation, and dispute resolution mechanisms in case of problems. Potential discrepancies may arise if the specifications of the goods are unclear, the delivery time is uncertain, or there are provisions that may disadvantage one of the parties. Therefore, it is important to ensure that the terms and conditions in Tokopedia 's pre-order   feature explicitly fulfill the legal pillars and conditions of the salam contract, in order to provide legal certainty and sharia compliance for all parties involved in the transaction.